The rise of children's book reviewing in America, 1865-1881, - Darling, Richard L., 1925- (Bowker, 1968)
A history of the early years of children's book reviewing which includes an analysis of trends in publishing, a survey of periodicals which reviewed juvenile literature, and an extensive bibliography of reviews appearing between 1865-1881.